Foreign banks and the doom loop - Ugo Albertazzi; Jacopo Cimadomo; Nicolò Maffei-Faccioli (Norges Bank, 2022)
This paper explores whether foreign banks stabilise or destabilise lending to the real economy in the presence of sovereign stress in the domestic economy and abroad. In this context, the presence of foreign intermediaries poses a fundamental, yet unexplored, trade-off. On the one hand, domestic sovereign shocks are broadly inconsequential for the lending capacity of foreign banks, given that their funding conditions are not hampered by such shocks. On the other, these intermediaries may react more harshly than domestic banks to a deterioration in local loan risk and demand conditions, or import shocks from their own sovereign. We exploit granular and confidential data on euro area banks operating in different countries to assess this trade-off. Overall, it is found that, under certain conditions, the presence of foreign lenders stabilises lending, thus mitigating the doom loop.
hdl:11250/2997492
Keywords: E5; G21; 330; Sovereign stress; International banks; Lending activity